CORRELATIONS BETWEEN CLUSTER DIFFERENTIATION 4 COUNTS, HUMAN IMMUNODEFICIENCY VIRUS CLINICAL STAGES, AND HEMOGLOBIN LEVEL AMONG HUMAN IMMUNODEFICIENCY VIRUS PATIENTS WITH ANEMIA IN MERPATI CLINIC, WANGAYA HOSPITAL, DENPASAR, BALI, INDONESIA: A CROSS-SECTI - SURYANA, KETUT; SUHARSONO, HAMONG; BUDIASA, GEDE; ANTARA, JARWA; ASTUTI, PUJI; INDAH, IDA AYU; STUTI, PUTRI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to determine the correlation between cluster of differentiation 4 (CD4) counts, human immunodeficiency virus (HIV) clinical stages, and hemoglobin (Hb) level among HIV-infected patients with anemia. Methods: A cross-sectional study was conducted in November 2017 at Merpati Clinic of Wangaya Hospital, Denpasar, Bali, Indonesia. We selected 79 HIV patients with anemia to participate in our study. We grouped CD4 counts into two categories: <200 cells/μL and ≥200 cells/μL, and we classified the HIV clinical stages into HIV and acquired immunodeficiency syndrome (AIDS). Results: About 55.7% (44) of men and 44.3% (35) of women were participated in this study. As many as, 91.1% (72) of participants were AIDS patients. The mean Hb was 8.77 g/dl with SD 1.79 g/dl. 81% (64) of study participants were suffered from anemia on chronic disease or inflammatory anemia, and 19% (15) of study participants were suffered from iron deficiency anemia. The median for CD4 counts was 94 cells/μL (3–309 cells/μL) with as many as 78.5% (62) of participants were found to have low CD4 counts (<200 cells/μL). Spearman analysis revealed a positive correlation between CD4 counts and Hb level (r=0.427, p<0.001). Independent sample t-test analysis found a correlation between the HIV clinical stages and Hb level. There was a difference between the mean of Hb level in each stage with the average difference of 0.8 g/dl (95% confidence interval 0.04–1.6; p<0.04). Conclusions: There is a correlation between CD4 counts, HIV clinical stages, and Hb level among HIV patients with anemia.